Ligation activity of fragmented ribozymes in frozen solution: implications for the RNA world - Vlassov, Alexander V. (Oxford University Press, 2004)
A vexing difficulty of the RNA world hypothesis is how RNA molecules of significant complexity could ever have evolved given their susceptibility to degradation. One way degradation might have been reduced is through low temperature. Here we report that truncated and fragmented derivatives of the hairpin ribozyme can catalyze ligation of a wide variety of RNA molecules to a given sequence in frozen solution despite having little or no activity under standard solution conditions. These results suggest that complex RNAs could have evolved in freezing environments on the early earth and perhaps elsewhere.